Pengawasan Tata Usaha dalam Meningkatkan Pelayanan Administrasi di MTs Negeri 5 Tabalong Kalimantan Selatan - Syafi’i, Imam (Published by the Postgraduate Program in Islamic Education Management, Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, Indonesia, 2022)
The existence of this research is to 1) find out the administrative supervision process in improving administrative services at MTsN 5 Tabalong 2) find out the administrative obstacles in supervising administrative services at MTsN 5 Tabalong. The method used is a qualitative approach with the type of case study research. 1) the administrative supervision process in improving administrative services at MTSN 5 Tabalong with the supervision carried out by the administrative head and madrasa head makes each staff have the initiative to change the quality on themselves, to run services better 2) as for the obstacles/ obtacles faced by the administration in supervising administrative services at MTsN 5 Tabalong in the form of HR aspects which still experience a shortage of educational staff, for the aspect of facilities and infrastructure there is still no hall, laboratory room, and library.